Vir a ser : a escritora, a narrativa e a personagem em formação - Müller, Annie Piagetti (2018)
There are two projects. A fiction one, which is a novel called Sozinhos, that tells the development of a character and its transformation from girl to woman. And the theoretical, an essay about the evolution of the writer during the experience of taking a Master in Creative Writing and the creation of the story. Both are presented with the intersections that exists between them, in the shape of reflections and exercises about the doubts and battles experienced during the continuous movement of becoming a writer and writing literature.